Umar Bin Khattab's Political and Economic Thoughts (Review of Political and Economic Studies in Historical Perspective) - Muhammad Iqbal; Afaf Fitriati; Maratus Solihah; Mashudi (Al-Iffah: Journal of Islamic Sciences Research, 2025)
Known for his political and economic reforms, Umar ibn Khattab was one of the greatest caliphs in Islamic history. This study looks at Umar bin Khattab's economic and political theories and how they affected society at the time. In the political aspect, Umar emphasized justice, openness, and community participation in government, by enforcing the syura (deliberation) system and creating policies that consider the well-being of the populace. Regarding the economy, Umar introduced various fiscal policies such as the management of zakat, baitul mal, and fair land distribution. This study uses a literary study approach, in which scholars gather information from books, journals, and articles, among other sources. The study's findings indicate that Umar bin Khathab's political-economic thoughts provide a strong foundation for the formation of a just and prosperous state, and are relevant to contemporary political and economic challenges.